Factors Affecting Happiness Among Students of Rawalpindi Medical University: A Cross-Sectional Study - Hassan Javed , Hassan Javed; Danish Arshad, Danish Arshad; Ali Imran Dhillon, Ali Imran Dhillon; Anser Ikram Rishi, Anser Ikram Rishi; Syed Muhammad Jawad Zaidi, Syed Muhammad Jawad Zaidi; Muhammad Kashif, Muhammad Kashif (Students' Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Happiness is among fundamental concepts in mental health that influence many aspects of life. It becomes particularly more important for people who are working under continuous stress especially medical students. This study was conducted to identify different factors and find out their effectiveness in predicting happiness scores among medical students of Rawalpindi Medical University. Methods: A cross-sectional study was conducted among students of Rawalpindi Medical University with ethical approval from institution. Stratified random sampling was used to select the participants. Data was collected using two questionnaires. First was Oxford Happiness Questionnaire and a second questionnaire included various variables being tested. SPSS V23 was used to analyse data. Results: A total of 450 students were enrolled including 297 females and 153 males. The Mean ± SD value of happiness of the participants was 4.01 ± 1.12. There was significant relationship between the happiness scores and physical activity, fulfilling religious obligations and participation in social activities while there was no significant relationship between happiness and gender, frequency of playing video games and listening to music and Facebook usage. Conclusion: The mean value of happiness among students of RMU coincided with average happiness scores in general population. Those participants of study who had increased physical activity by either doing exercise or going to gymnasium had significantly higher scores of happiness. Similarly, individuals who were fulfilling religious obligations and had increased participation in social activities also scored significantly higher on happiness scale. Key Words: Happiness score, Physical activity, Medical students, Social activities, Religious obligations.